Development of nanoantibiotic delivery system using cockle shell-derived aragonite nanoparticles for treatment of osteomyelitis - Saidykhan, Lamin; Abu Bakar @ Zakaria, Md Zuki; Rukayadi, Yaya; Kura, Aminu Umar; Saiful Yazan, Latifah (Dove Medical Press, 2016)
A local antibiotic delivery system (LADS) with biodegradable drug vehicles is recognized as the most effective therapeutic approach for the treatment of osteomyelitis. However, the design of a biodegradable LADS with high therapeutic efficacy is too costly and demanding. In this research, a low-cost, facile method was used to design vancomycin-loaded aragonite nanoparticles (VANPs) with the aim of understanding its potency in developing a nanoantibiotic bone implant for the treatment of osteomyelitis. The aragonite nanoparticles (ANPs) were synthesized from cockle shells by a hydrothermal approach using a zwitterionic surfactant. VANPs were prepared using antibiotic ratios of several nanoparticles, and the formulation (1:4) with the highest drug-loading efficiency (54.05%) was used for physicochemical, in vitro drug release, and biological evaluation. Physiochemical characterization of VANP was performed by using transmission electron microscopy, Fourier transform infrared spectroscopy, X-ray powder diffraction, and Zetasizer. No significant differences were observed between VANP and ANP in terms of size and morphology as both samples were cubic shaped with sizes of approximately 35 nm. The Fourier transform infrared spectroscopy of VANP indicated a weak noncovalent interaction between ANP and vancomycin, while the zeta potential values were slightly increased from -19.4±3.3 to -21.2±5.7 mV after vancomycin loading. VANP displayed 120 hours (5 days) release profile of vancomycin that exhibited high antibacterial effect against methicillin-resistant Staphylococcus aureus ATCC 29213. The cell proliferation assay showed 80% cell viability of human fetal osteoblast cell line 1.19 treated with the highest concentration of VANP (250 µg/mL), indicating good biocompatibility of VANP. In summary, VANP is a potential formulation for the development of an LADS against osteomyelitis with optimal antibacterial efficacy, good bone resorbability, and biocompatibility.